2014
DOI: 10.1080/10538712.2014.931319
|View full text |Cite
|
Sign up to set email alerts
|

Perpetration, Revictimization, and Self-Injury: Traumatic Reenactments of Child Sexual Abuse in a Nonclinical Sample of South African Adolescents

Abstract: Risk factors for traumatic reenactments of child sexual abuse experiences (perpetration, revictimization, and self-injury) were examined in a sample of 718 South African secondary school adolescents. Logistic regression analyses indicated that the most consistent predictors of reenactments were a history of child sexual abuse (rape and/or indecent assault) and respondents' gender, with males being significantly more likely than females to report perpetration (OR = 13.5) and females being more likely to report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Most research to date has focused on the relationship between different forms of violence in urban areas or in specific populations, such as women in antenatal clinics (Dunkle et al, 2004) and young adults (Penning & Collings, 2014), with little research conducted in representative, rural communities (Gass et al, 2011; Richter et al, 2014). Specifically, little is known about potential associations between experiencing different types of violence in childhood and vulnerability to IPV and nonpartner sexual violence victimization and perpetration among individuals in rural communities (Dutton & Nicholls, 2005; Wilkins, Tsao, Hertz, Davis, & Klevens, 2014), including rural South African communities.…”
mentioning
confidence: 99%
“…Most research to date has focused on the relationship between different forms of violence in urban areas or in specific populations, such as women in antenatal clinics (Dunkle et al, 2004) and young adults (Penning & Collings, 2014), with little research conducted in representative, rural communities (Gass et al, 2011; Richter et al, 2014). Specifically, little is known about potential associations between experiencing different types of violence in childhood and vulnerability to IPV and nonpartner sexual violence victimization and perpetration among individuals in rural communities (Dutton & Nicholls, 2005; Wilkins, Tsao, Hertz, Davis, & Klevens, 2014), including rural South African communities.…”
mentioning
confidence: 99%
“…For example, symptoms of depression, anxiety, and PTSD have been found to increase the risk of revictimization in youth and adult samples (Auslander, Tlapek, Threlfall, Edmond, & Dunn, 2015; Cuevas, Finkelhor, Clifford, Ormrod, & Turner, 2010; McCart et al, 2012; Wolfe, Wekerle, Scott, Straatman, & Grasley, 2004). Maladaptive, abuse-related cognitions such as self-blame, loss of trust, and negative self-appraisals (Penning & Collings, 2014) stemming from initial abuse experiences, and health risk behaviors including substance and alcohol use, unprotected sex, prostitution, and having frequent sexual partners (Fergusson, Horwood, & Lynskey, 1997; Krahe, Scheinberger-Olwig, Waizenhofer, & Kolpin, 1999; Testa, Hoffman, & Livingston, 2010) also place individuals at heightened risk.…”
mentioning
confidence: 99%
“…Although the present findings provide preliminary support for a cognitive-mediation model of posttraumatic outcomes, further research is indicated in order to assess the mediating effects of cognitive appraisals on other posttraumatic outcomes (e.g., depression, anxiety disorders, and posttraumatic re-enactment behaviours) which have been found to be associated with traumatic exposure (cf. Penning & Collings, 2014; Ward, Flisher, Zissis, & Lombard, 2001). Furthermore, given that many cases of child maltreatment involve exposure to multiple forms of victimization (Dong et al, 2004) – including poly-victimization (Finkelhor, Ormrod, & Turner, 2007), chronic victimization (Courtois & Ford, 2009), and/or continuous victimization (Eagle & Kaminer, 2013) – further research would appear to be indicated in order to more systematically explore the mediating effects of trauma-related appraisals on posttraumatic outcomes in the aftermath of (or in the context of) multiple forms of exposure to child maltreatment.…”
Section: Resultsmentioning
confidence: 99%